2000
DOI: 10.1002/(sici)1521-3749(200006)626:6<1279::aid-zaac1279>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Materials with Large Channels or Cavities - Synthesis and Crystal Structure of an Iron(III) tetra(4-carboxyphenyl)-porphine

Abstract: Tetra(4‐carboxyphenyl)‐porphine iron(III) chloride · 2 CH3COOH · 4 H2O (1) was prepared via a hydrothermal synthesis approach starting from FeCl2 and 5,10,15,20‐tetrakis‐(4‐carboxyphenyl)‐21 H,23 H‐porphine in glacial acetic acid in the presence of KOH as a base and ytterbium(III) acetate as a template. Compound 1 was characterized by single crystal X‐ray diffraction and elemental analysis. Space group: P 1, Z = 2, unit cell dimensions at 200 K: a = 9.282(2), b = 20.239(5), c = 22.239(5) Å, α = 92.49(3), β = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Especially, their ease of functionalization is of particular interest as it has been clearly demonstrated that tailoring the nature of the substituent or the central metallic ion allows fine-tuning the properties of these metalloligands. It results that the porphyrinic (or phthalocyanines) derivatives appear as attractive building blocks for the preparation of functional hybrid porous solids. Particularly, since the 1990s, many attempts have been reported in order to build up open coordination frameworks based on linkers derived from porphyrins. However, examples of materials stable upon solvent removal and exhibiting a permanent porosity detected by gas sorption are still scarce. More precisely, several solids based on the tetratopic 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP, see Figure a) anionic linker, which can give rise to stable neutral frameworks, have been reported. For instance, the groups of Goldberg, Choe, , and Kempe , published many examples of two- and three-dimensional open frameworks constituted by the TCPP linker and various metallic ions, but no permanent porosity was evidenced in these solids. Another noticeable study was reported by the group of Suslick, with a 3-D solid based on the Co II -TCPP porphyrinic building block that shows interesting selective adsorption of different liquids, although nitrogen sorption experiments revealed a low BET surface area (125 m 2 g –1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, their ease of functionalization is of particular interest as it has been clearly demonstrated that tailoring the nature of the substituent or the central metallic ion allows fine-tuning the properties of these metalloligands. It results that the porphyrinic (or phthalocyanines) derivatives appear as attractive building blocks for the preparation of functional hybrid porous solids. Particularly, since the 1990s, many attempts have been reported in order to build up open coordination frameworks based on linkers derived from porphyrins. However, examples of materials stable upon solvent removal and exhibiting a permanent porosity detected by gas sorption are still scarce. More precisely, several solids based on the tetratopic 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP, see Figure a) anionic linker, which can give rise to stable neutral frameworks, have been reported. For instance, the groups of Goldberg, Choe, , and Kempe , published many examples of two- and three-dimensional open frameworks constituted by the TCPP linker and various metallic ions, but no permanent porosity was evidenced in these solids. Another noticeable study was reported by the group of Suslick, with a 3-D solid based on the Co II -TCPP porphyrinic building block that shows interesting selective adsorption of different liquids, although nitrogen sorption experiments revealed a low BET surface area (125 m 2 g –1 ).…”
Section: Introductionmentioning
confidence: 99%
“…73À75 More precisely, several solids based on the tetratopic 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP, see Figure 1a) anionic linker, which can give rise to stable neutral frameworks, have been reported. For instance, the groups of Goldberg, 76À80 Choe, 81,82 and Kempe 83, 84 published many examples of two-and three-dimensional open frameworks constituted by the TCPP linker and various metallic ions, but no permanent porosity was evidenced in these solids. Another noticeable study was reported by the group of Suslick, 85 with a 3-D solid based on the Co II -TCPP porphyrinic building block that shows interesting selective adsorption of different liquids, although nitrogen sorption experiments revealed a low BET surface area (125 m 2 g À1 ).…”
Section: ' Introductionmentioning
confidence: 99%
“…In this simplest case, the electron donor−acceptor distances for reactions 1 (1) and 1 (2) were estimated from the distances between the metal center and the carboxyl oxygen in the crystal structures of iron(III) tetra-4-carboxyphenylporphyrin chloride 30 and silver(II) 5,10,15,20-tetrakis(4-carboxy-2,6-dimethylbiphenyl)porphyrin, 31 respectively. Inserting the relative difference R ̃(1) − R ̃(2) = −4.2 Å and the experimental values for k 1 (1) and k 1 (2) into eq 9 gave β = 0.26 ± 0.04 Å −1 .…”
mentioning
confidence: 99%
“…The lack of specific intralayer interactions between planar porphyrin cycles makes the unrestricted swelling of porphyrin‐sponges when including guests, thus resulting in molecule discrimination with poor efficiency. Besides, solvents or counter ions could disturb hydrogen bonds between discrete metalloporphyrin [87] …”
Section: Rational Design Of Hybrid Hofsmentioning
confidence: 99%
“…Besides, solvents or counter ions could disturb hydrogen bonds between discrete metalloporphyrin. [87] Although Goldberg's group designed the porphyrin-sieve with fixed-size tunable cavities and high porosity, preparing metal-porphyrin HOFs with permanent porosity remains challenging. [88] HOF-7, reported in 2015, is the first metalporphyrin HOF with permanent porosity.…”
Section: Hybrid Hofs Containing Metal-porphyrin Complexesmentioning
confidence: 99%